2007
DOI: 10.1002/chin.200725222
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Metallomolecules as Agents for the Control of DNA Structure

Abstract: DNA is often referred to as the molecule of life, since it contains the instructions for making the required proteins. However, it is not simply a (genetic) code to be read; its structure has an important role in determining when and how much of a particular 5 protein is made at any point in time. Furthermore, there are a range of special DNA structures, e.g. Holliday junctions, which play essential roles for the existence of life as we know it or as it will become. In this tutorial review the normal B-DNA str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…109 The intercalation decreases the DNA helical twist and lengthens the DNA. 110,111 Traditionally, it has been thought that only molecules with fusedring structures could be good intercalators. But it was later found that the presence of basic, cationic, or electrophilic functional groups is often necessary for a compound to be a good intercalator, while the fused-ring structures are not always required.…”
Section: Intercalating Into Dnamentioning
confidence: 99%
“…109 The intercalation decreases the DNA helical twist and lengthens the DNA. 110,111 Traditionally, it has been thought that only molecules with fusedring structures could be good intercalators. But it was later found that the presence of basic, cationic, or electrophilic functional groups is often necessary for a compound to be a good intercalator, while the fused-ring structures are not always required.…”
Section: Intercalating Into Dnamentioning
confidence: 99%
“…A definition found in several references arises from polymer curvature. Persistence length is defined to be the length along the polymer after which the average deflection of the tangent is 1 radian 4,16 . That is, hjfji ¼ 1 where f is the angle between two tangents a persistence length apart along the polymer.…”
Section: Definition 4: Curvature Definition Of Persistence Lengthmentioning
confidence: 99%
“…There are various types of interaction mechanisms between DNA and drug molecules including non-covalent groove binding, covalent binding / cross-linking, DNA cleaving and intercalation (20)(21)(22)(23). Intercalator molecules accumulate in hydrogen bounds of double stranded DNA (dsD-NA) due to their planar aromatic rings structure and are stacked themselves between bases (24).…”
Section: Introductionmentioning
confidence: 99%